Relationship of Demographic Variables and Level of Disease Awareness Among Systemic Lupus Erythematosus Patients; a Tertiary Care Hospital Study - Shahzadi, Sobia; Samreen, Saba; Salim, Babur; Mushtaq, Samina; Khan, Zafar Ayub; Nasim, Amjad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the relationship between demographic variables and the level of disease awareness among patients of Systemic lupus erythematosus (SLE). Study Design: Cross-sectional study Place and Duration of Study: Fauji Foundation Hospital, Rawalpindi Pakistan, from Mar 2019 to Jan 2020. Methodology: The study included 150 patients, diagnosed with systemic lupus erythematosus according to SLICC criteria. A self-made questionnaire was used, including three sets of questions. The first set collected information on socio-demographic characteristics, and the second set gathered information regarding the symptoms and treatment. While, the third was based on aetiology, aspects of life affected and sources of disease knowledge. Results: A total of 150 participants’ data was analysed; the majority of those were females. The mean age was 36.19±12.08 years and 17.3% of the patients had adequate knowledge of the disease. There were no statistically significant differences in awareness based on gender, education level and geographical distribution. Conclusion: SLE is a two-pronged sword that affects patients’ mental and physical health. Patient awareness remains an important aspect of disease management which is currently not emphasized appropriately. At the community and national levels, measures must be taken to promote and create awareness regarding SLE.